Capacity configuration optimization of electricity heat hydrogen regional integrated energy system considering supply-demand uncertainties. - Tianhe Sun; Runqi Sun; Xiaoyi Qian; Baoshi Wang (PLoS ONE)
Rationally configuring the capacity of the electricity heat hydrogen regional integrated energy system is conducive to improving its economy and energy utilization efficiency. In view of the dual effects of the uncertainties of energy supply and demand in system configuration on power supply reliability and wind power consumption, a min-max-min two-stage robust optimization configuration model aiming at the minimum sum of system investment and operating cost is established for achieving an optimal capacity configuration of multi-vector technologies involved in it. On the basis of typical scenarios, a box-type uncertainty set independent of a probability distribution is used to describe the uncertainty of wind power and demand and the robustness constraint is formed. An innovative parameter, named the uncertainty adjustment parameter, is introduced into the box-type uncertainty set to avoid sacrificing economic benefits caused by too conservative configuration scheme. In this paper, the column and constraint generation algorithm and strong duality theory are used to decompose the original problem into the linearized master problem and subproblem, which can improve the solving speed. Finally, an integrated energy system in the north of China is taken as a case study. The results demonstrate that the proposed model effectively addresses the uncertainty problems of wind power and demand, leading to improved reliability and wind power integration performance. By changing the uncertainty adjustment parameter, the conservativeness of the configuration scheme can be flexibly adjusted. The effectiveness and applicability of the proposed model and solution algorithm are verified.